Peningkatan Motivasi Dan Kemampuan Mengajar Guru Melalui Unconscious Mind Program - Takdirmin; Randy Saputra Mahmud (Almeera Education, 2022)
The Unconscious Mind Program (UMP) is an approach that can use to improve student learning outcomes by incorporating suggestions into students' subconscious minds. The teachers use structured relaxation, attractive visual images, metaphors, movements, music, and suggestions in UMP learning. This study aims to determine the motivation and ability of teachers to implement UMP learning. This research is a type of CAR using 15 teacher subjects at SMPN Bantaeng. This research was conducted in two cycles, each of consisted of planning, implementation, observation, and reflection stages. The result is that the dominant teacher has been able to apply the UMP, although there are still a small number of teachers who are only able to apply 75% of the overall UMP implementation indicators. The application of UMP can make teachers' motivation high in carrying out learning in the classroom with an average motivation score of 3.61 from a maximum score of 4.00.